IN THE DEVIL’S DEEP DUNGEON; IN SEARCH OF THE SPIRIT OF EVIL IN THE MINES OF THE ANDES - Giambelli, Rodolfo A. (L’Uomo società tradizione sviluppo, 2019)
The miners of Oruro, Bolivia, worship Tio as the spirit of the mines they work in, depicting him in the form of the devil of Western iconography. In exchange for goods and sacrifice, Tio gives the miners the ore; usually a llama or other animal is the price of the sacrifice, but occasionally he demands even the blood and life of the miners. Fatal accidents are interpretated by the miners as Tio’s price for more ore. This last sacrifice demonstrates the evil nature of the spirit of the mine. The author compares a former interpretation of M. Taussig with historical data concerning mines and mining in Andean societies since the Inca empire and with a detailed analysis of the symbolism of the devil in relation to the traditional Andean system of belief and the superimposed Christian religious doctrine. The author’s central thesis is that Tio does not bear the morally negative character that Taussig reads into him; his significance is deeply rooted in traditional Andean dualism, and we need to distinguish between the Western symbolism of evil and the meaning that this iconography may assume in different societies. The image of Tio in Andean societies is closely linked to the symbolism of the spirit of nature and to the dead and they all carry the characteristic of danger as well as of goodness and fertility. The author also argues that Tio worship is not an expression of the miners’s past heritage in the face of their inability to free themselves from the peasant world view, but that this ritual is very much perceived and lived as a shared experience which can shape the miners’ class consciousness against the disgregating pressure of capitalist relations of production. Sommario I minatori di Oruro - Bolivia — venerano in Tio lo spirito possessore delle miniere in cui essi lavorano, rappresentato sotto le forme del diavolo nell’iconografia occidentale. In scambio di beni e sacrifici Tio concede l’estrazione del minerale; generalmente un lama o un altro animale è il prezzo del sacrificio ma occasionalmente Tio chiede di piu: domanda il sangue e la vita dei minatori stessi. Gli incidenti mortali sul lavoro sono interpretati dai minatori come il prezzo che Tio esige per una maggiore quantita di minerale estratto; quest’ultimo sacrificio mette in luce la natura malvagia dello spirito della miniera. L’autore confronta una precedente interpretazione di M. Taussig sia con un nucleo di dati storici relativi all’attivita mineraria nella societa andina a partire dal periodo Inca, che con un’analisi della simbologia legata alla figura del diavolo nel sistema culturale andino e in relazione alla dottrina cristiana successivamente imposta su quest’ultimo. Tesi centrale dell’articolo é che in Tio non si puo ravvisare il carattere moralmente negativo che M. Taussig vuole leggere in questa figura. Il significato che assume Tio é profondamente radicato nel tradizionale dualismo andino ed è necessario distinguere tra la simbologia con cui l’occidente esprime l’idea del male e il significato che questa iconografia può assumere in differenti societa. L’immagine di Tio nella societa andina é legata sia alla simbologia propria degli spiriti/dei del mondo naturale che dei morti, entrambi questi elementi sono portatori sia dei caratteri di pericolosita che di bonta e fertilita. Attraverso l’analisi si evince inoltre che la venerazione di Tio non è semplicemente un’espressione dell’eredita culturale dei minatori di fronte alla loro inabilità di svincolarsi da una visione della realta caratteristica del mondo contadino; bensì che questo rituale é percepito e vissuto come un momento in grado di formare la coscienza di classe dei minatori contro la disgregante pressione imposta dalle relazioni di produzione del mondo capitalista.